2019
DOI: 10.1016/j.athoracsur.2019.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Second Primary Lung Cancers Demonstrate Similar Survival With Wedge Resection and Lobectomy

Abstract: Background. Patients who have undergone curative surgery for stage I lung cancer require continued surveillance owing to the risk of a second primary lung cancer developing. Early diagnosis allows for prompt intervention. However, as in primary cancers, the role of wedge vs lobar resections remains controversial.Methods. The Surveillance Epidemiology and End Results database was examined from 2004 to 2012 and all pathologically proven stage I lung cancer patients who underwent cancer-directed surgery were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…21 However, Lee et al concluded that there were similar survival benefits between wedge resection and lobectomy for SPLC. 18 In our study, it seemed that lobectomy for IPLC performed slightly better in survival than sublobar resection, but without significance (Fig 4a). Similarly, there was also no significant difference among the three surgical procedures (wedge resection, segmentectomy and lobectomy) for SPLC (Fig 4b).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…21 However, Lee et al concluded that there were similar survival benefits between wedge resection and lobectomy for SPLC. 18 In our study, it seemed that lobectomy for IPLC performed slightly better in survival than sublobar resection, but without significance (Fig 4a). Similarly, there was also no significant difference among the three surgical procedures (wedge resection, segmentectomy and lobectomy) for SPLC (Fig 4b).…”
Section: Discussionmentioning
confidence: 52%
“…It seemed that fewer males intended to suffer SPLC after surgery for IPLC (272 vs. 393), but males showed worse overall survival than females (HR = 1.82, 95% CI: 1.29-2.59, P = 0.001), which was similar to that reported in a previous study. 18 Surprisingly, in our study, the characteristics of resected IPLC could influence the survival outcome of SPLC patients. Patients with IPLC having SCC demonstrated a worse survival than those with ADC (HR = 1.89, 95%CI: 1.17-3.04, P = 0.009).…”
Section: Discussionmentioning
confidence: 54%
“…For stage IA SP-NSCLC patients with previous lung cancer-directed surgery, to date, it has not been fully understood whether lobectomy is more conducive to survival than wedge resection. Although several retrospective studies [16][17][18] and a recent SEER-based study [11] have found that lobectomy did not show a signi cant survival advantage over sublobectomy for SPLC patients, these researches still lacked an indepth study on SPLC patients who have undergone radical surgery for primary lung cancer. To better solve this problem and provide references for further clinical research and practice, we carried out this study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite signi cant breakthroughs in the diagnosis and treatment of lung cancer, it has not been determined whether lobectomy has a better survival advantage than wedge resection for patients with early-stage SP-NSCLC, especially those with history of radical surgery for the rst primary lung cancer (FPLC). A recent SEER-based study [11]has reported that SPLC demonstrated similar survival with lobectomy and wedge resection. However, the study did not delve into the differences in survival between the two procedures in various speci c circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Shimada et al 84 recommended to resect main cancers (larger size or radiologically invasive) with lobectomy and sub-cancers (any other lung cancers) with sublobectomy. Although Zuin et al 4 revealed lobectomy was superior to sublobectomy for second primary lung cancer with better 5-year survival (57.5% vs 36%; p=0.016), others 8,94 proposed that sublobar resection for the second cancer was safe with acceptable mortality and a 5-year survival rate, especially for patients with limited pulmonary function.…”
Section: Alternative Treatment Options Surgery: Unknown Optimal Procementioning
confidence: 99%